Without you : children and young people growing up with loss and its effects - Granot, Tamar (Jessica Kingsley Publishers, 2005)
Adults often believe that children are quick to overcome and forget loss, but there is evidence that children are affected by the memory and impact of loss throughout their lives, and especially during the years that they grow-up. In this sympathetic book, Tamar Granot explains the immediate and long-term effects of loss on children and adolescents. She describes how loss is experienced at different ages, explains the significant consequences it can have at each stage of the children's development and the effects it might have on the development of their personality. The author describes how t.